Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3748/wjg.v17.i13.1694
|View full text |Cite
|
Sign up to set email alerts
|

Legalon-SIL downregulates HCV core and NS5A in human hepatocytes expressing full-length HCV

Abstract: Our results demonstrate that treatment with LS downregulates HCV core and NS5A expression in CON1 cells which express full length HCV genotype 1b, and suggests that LS may prove to be a valuable alternative or adjunctive therapy for the treatment of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…They reported that increased expression of HO-1 is associated with diminished HCV replication and also with an increase of the resistance of hepatocytes to oxidative damage. Based on this findings, heme oxygenase regulation could be useful as an adjunctive antiviral therapy [62][63][64] .…”
Section: Heme Oxygenase Regulationmentioning
confidence: 88%
See 1 more Smart Citation
“…They reported that increased expression of HO-1 is associated with diminished HCV replication and also with an increase of the resistance of hepatocytes to oxidative damage. Based on this findings, heme oxygenase regulation could be useful as an adjunctive antiviral therapy [62][63][64] .…”
Section: Heme Oxygenase Regulationmentioning
confidence: 88%
“…On the other hand, HCV is potentially lymphotropic, because it can invade and propagate in cells of the [47,48] 400-544 IU/d or 600 mg 1 Vitamin C [48] 500 mg-10 g N-acetylcysteine [78] 600 mg or 1800 mg/d 1 Mitoquine Q [65,66] 40 or 80 mg/d α-tocopherol [79] 600 mg, 500 mg/d, 800 IU/d Glycyrrhizin [40,42,53,54] 500 mg, 120 mg Different mechanisms Silymarin (Silibinin A, Silibinin B, etc.) [40,64,[80][81][82] 250 mg or 5-20 mg/kg 1 S-adenosylmethionine [69] 1600 mg/d 1 Acetylsalicylic acid [73] 4 mmol/L (in vitro) Gallic acid 300 mg/mL (in vitro) 1 Combined treatment with interferon.…”
Section: Antioxidant Therapymentioning
confidence: 99%
“…Finally, the antiviral action of silybin against HCV replication is also related to its antioxidant properties. In fact, silybin reduces the levels of some free radical species produced during HCV gene expression, and in this manner it interferes with the regulation of some proteins of the HCV core (for example, downregulation of HMOX-1 mRNA and upregulation of Nrf2 protein) necessary for HCV replication [59].…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 over-expression has been observed to decrease HCV replication, reduce pro-oxidant production in replicon cells, and increase resistance to oxidative injury [52] . These findings strongly suggest potential therapeutic roles for HO-1 [53] .…”
Section: Ho-1 As a Potential Therapeutic Target In Liver Diseasesmentioning
confidence: 99%